"Acquired brain injury and return to work": the feasibility of a training program for insurance physicians. Issue 10 (7th May 2020) - Donker-Cools, Birgit H. P. M.; Wind, Haije; Frings-Dresen, Monique H. W.
Abstract: Purpose: To study the feasibility (limited efficacy, acceptability, and implementation) of a training program for insurance physicians. Methods: Limited efficacy was evaluated over time (T0–T2) by conducting knowledge question tests using realistic case scenarios, analyzed by non-parametric Friedman and Wilcoxon signed-rank tests. Acceptability was evaluated by asking participants to agree or disagree with statements; for example, the knowledge was "relevant, " "useful, " or "appropriate." Answers were analyzed using descriptive statistics. Open-ended questions were used to ask participants what, in their opinion, were the facilitators of and barriers to implementing the knowledge taught. Their answers were coded and categorized. Results: Fifty-one IPs participated in the study. Concerning limited efficacy: the median values of the knowledge scores increased significantly over time and between time points from 16 (T0) to 21 (T1) and 32 (T2), p  < 0.00. Concerning acceptability: 46 of 47 respondents perceived the training program to be "relevant, " "useful, " and "appropriate"; 44 respondents intended to use it in practice. Concerning implementation: participants reported "training" and "utility" as examples of facilitators and "lack of time, " for example, as a barrier. Conclusion and implications: The feasibility (limited efficacy, acceptability, implementation) of the training program is demonstrated; the training program can be applied in practice. Implications for rehabilitation: The "acquired brain injury and return to work" training programme can be applied in postgraduate teaching and continuing medical education for insurance physicians. Interactive teaching methods including realistic case scenarios with a link to practice are recommended to provide insurance physicians the opportunity to learn to apply and discuss new knowledge and effectively improve insurance physicians' knowledge. Implementation of a training programme for insurance physicians can be facilitated if a brief summary of the imparted knowledge is available. Barriers, such as "other occupational healthcare and paramedical professionals being unfamiliar with the imparted knowledge" need to be addressed when implementing the "acquired brain injury and return to work" training programme.